An FPGA-based system for real-time monitoring of voltage harmonics - Erişti, Belkis; Yildirim, Ozal; Erişti, Hüseyin; Demir, Yakup (My University, 2013)
In this study, a real-time monitoring system has been prepared by using Field Programmable Gate Arrays (FPGA) in order to monitor three phase voltage harmonics instantly. In this monitoring system, a signal input card has been designed for the purpose of transferring three phase voltage signals of the network to the FPGA card. Harmonic values of the voltage signals belonging to each phase have been instantly calculated with the 128 floating point FFT algorithm embedded in the FPGA card. The obtained harmonic values are transferred onto computer with the RS232 communication protocol created in the FPGA device. A software featuring a graphical interface has been prepared on the computer for the purpose of visually displaying the voltage signals and the harmonic data belonging to the voltage signals. All the parameters regarding the monitoring system can be monitored easily on this software. The monitoring system that was designed for the present study was set up and tested in the laboratory at the Department of Electrics and Electronics Engineering, Tunceli University. The results show that the monitoring system can successfully obtain the voltage signals and the harmonic values of these signals.
19th IMEKO TC4 Symposium - Measurements of Electrical Quantities 2013 and 17th International Workshop on ADC and DAC Modelling and Testing -- 18 July 2013 through 19 July 2013 -- Barcelona -- 102681
Keywords: FPGA; Harmonic; Monitoring; Power Quality